ASSESSMENT OF CYTOTOXIC AND IMMUNOMODULATORY PROPERTIES OF PIPER NIGRUM LINN. (WHITE PEPPER) SEED EXTRACT (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Macrophages are tissue-based phagocytes that play the central role in initiating defence mechanism of host immunity. Macrophage expresses inducible nitric oxide synthase (iNOS) that inhibit pathogen replication by releasing a variety of effector molecules which includes nitric oxide (NO). In the present study ethanol extract of Piper nigrum Linn. (white pepper) seed was investigated for its cytotoxicity and in vitro immunomodulatory properties using cell proliferation and NO determination assay with J774a-1, macrophage cell line. The ethanol seed extract was found to exhibit toxicity at higher concentrations of 50µg/ml and 100µg/ml. The seed preparation was observed to enhance both, the proliferation of macrophage cell with higher percentage proliferation of 29.24 at 12.5µg/ml and the production of NO with significant stimulation level of 47.74% at 12.5µg/ml compared to the control. Since the results show the modulator effect of Piper nigrum Linn. seed on macrophage cells, it could be considered to possess immunomodulatory potential.